2019
DOI: 10.11648/j.aff.20190805.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Level of Nitrogen Fertilizer on Growth, Yield and Yield Component of Tomato (<i>Lycopersicon Esculentum Mill</i>.) at West Showa Zone, Oromia, Ethiopia

Abstract: The field experiment was conducted in West showa zone, Toke kutaye district of Ormia region, Ethiopia with the objective to determine the optimum nitrogen fertilizer rate on different growth parameters, yield and yield component of tomato crop. To attain the objective, four level of nitrogen fertilizer Viz., 0, 50, 100, and 150 kg/ha were used as treatments. The experiment was laid out in randomized complete block design (RCBD) with three replications. Data on plant height, number of primary branches per plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Both the deficit and excess of N sources have negative impacts on plants: fruit production decreases, susceptibility to insect pests increases, and the nutritional quality of harvested products is reduced (Torres -Olivar et al, 2014). Previous studies have shown that increasing the N addition rate positively affects tomato growth and yield, and maximum fruit yield was reached under the higher N application rate from 100 to 160 kg N ha -1 (Aman & Rab, 2013;Etissa et al, 2013;Rashid et al, 2016;Beyene & Mulu, 2019). However, the studies of Parisi et al (2006) and Elia et al (2007) indicated that a greater fruit yield and yield attributes were recorded by adding 200 kg N ha -1 , and further increases of N rates did not affect tomato yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the deficit and excess of N sources have negative impacts on plants: fruit production decreases, susceptibility to insect pests increases, and the nutritional quality of harvested products is reduced (Torres -Olivar et al, 2014). Previous studies have shown that increasing the N addition rate positively affects tomato growth and yield, and maximum fruit yield was reached under the higher N application rate from 100 to 160 kg N ha -1 (Aman & Rab, 2013;Etissa et al, 2013;Rashid et al, 2016;Beyene & Mulu, 2019). However, the studies of Parisi et al (2006) and Elia et al (2007) indicated that a greater fruit yield and yield attributes were recorded by adding 200 kg N ha -1 , and further increases of N rates did not affect tomato yield.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, tomato yields are highly responsive to the addition of N (Warner et al, 2004). Beyene & Mulu (2019) reported that N promotes vegetative growth and fruit yield, favours fruit development, and the application of the proper N level has a dramatic effect on tomato growth and development. Both the deficit and excess of N sources have negative impacts on plants: fruit production decreases, susceptibility to insect pests increases, and the nutritional quality of harvested products is reduced (Torres -Olivar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, fertilizer rates, especially N and P were determined for tomatoes in some parts of Ethiopia. But the rate, for instance, the fertilizer recommendation for N ranged between 56 and 230 kg ha −1 and for P ranged from 48 to 137 kg ha −1 13 – 15 . The probable reason for this attributed to soil and agro-ecological variability.…”
Section: Introductionmentioning
confidence: 99%